Product market competition with differentiated goods and social welfare in the presence of an industry-wide union - Buccella, Domenico (2018)
Mainstream locus communis indicates that a more competitive product market leads to higher social welfare levels. Using a Conjectural Variation (CV) model, this research note analyzes the effects on welfare of different degrees of product market competition in a duopoly with differentiated goods. Bargaining between the firms and the industry-wide union occurs under the Efficient Bargaining (EB) model. The work indicates that, with close substitute goods, social welfare is maximized for the inter- mediate levels of market competition, whereas more independent goods lead to the standard result of a high welfare level under competitive markets.